ZOROASTRIAN BURIAL RITES OF THE SOUTHERN ARAL SEA REGION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to material culture The territory of the Southern Aral Sea region, in cultural and historical terms, in various historical periods was either a part or a territory under the cultural, political or economic influence of the ancient and medieval Khorezm, which, according to well-known written and archaeological sources, is firmly included in the circle of the Avestan geography, and, according to some scientists, is the most ancient center of the Zoroastrian religion.